Nathaniel Alexander Owings papers - Owings, Nathaniel Alexander, 1903-; Owings, Nathaniel Alexander, 1903-; Owings, Nathaniel Alexander, 1903-
Correspondence, memoranda, journals, minutes, speeches, writings, reports, notes, subject file, legal and financial records, biographical material, appointment calendars, clippings, scrapbooks, printed matter, charts, graphs, diagrams, photographs, and other papers documenting Owings's career as a founding partner of the architectural firm, Skidmore, Owings & Merrill; chairman of public commissions responsible for the redesign of Pennsylvania Avenue in Washington, D.C.; member of various commissions relating to conservation, preservation, and redevelopment in California; and author of works on the aesthetic and practical applications of architecture in contemporary life, architectural theory, and city planning. Includes material relating to his service on or contribution to the California Advisory Committee on a Master Plan for Scenic Highways, the Monterey coast master plan, the Pennsylvania Avenue Development Corporation, and the President's Council on Pennsylvania Avenue. Includes drafts of Owings's books, The American Aesthetic (1969) and The Spaces In Between: An Architect's Journey (1973); and material pertaining to his gold medal awarded by the American Institute of Architects in 1983 and his collection of kachina dolls made by Hopi Indians.
Correspondents include Ansel Adams, Stephen Davison Bechtel, Jerry Brown, Wolf von Eckardt, Arthur J. Goldberg, Lady Bird Johnson, Robert Moses, Daniel P. Moynihan, Elwood R. Quesada, David Rockefeller, Nicholas Roosevelt, Wallace Earle Stegner, and Stewart L. Udall.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Architect and engineer; died 1984.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Ansel, -- 1902-1984 -- Correspondence; Bechtel, Stephen Davison, -- 1925- -- Correspondence; Brown, Jerry, -- 1938- -- Correspondence; Eckardt, Wolf von, -- 1918- -- Correspondence; Goldberg, Arthur J. -- Correspondence; Johnson, Lady Bird, -- 1912-2007 -- Correspondence; Moses, Robert, -- 1888-1981 -- Correspondence; Moynihan, Daniel P. -- 1927-2003 -- Correspondence; Quesada, Elwood R. -- 1904- -- Correspondence; Rockefeller, David, -- 1915- -- Correspondence; Roosevelt, Nicholas, -- 1893-1982 -- Correspondence; Stegner, Wallace, -- 1909-1993 -- Correspondence; Udall, Stewart L. -- Correspondence; American Institute of Architects; California. -- Advisory Committee on a Master Plan for Scenic Highways; Pennsylvania Avenue Development Corporation; President's Council on Pennsylvania Avenue (U.S.); Skidmore, Owings & Merrill; Architectural firms; Architecture -- United States; Architecture -- Awards -- United States; City planning -- California; City planning -- United States; City planning -- Washington (D.C.); Conservation of natural resources -- California; Historic preservation -- California; Hopi Indians; Kachina dolls; Roadside improvement -- California; Urban beautification -- United States; Monterey Peninsula (Calif.); Pennsylvania Avenue (Washington, D.C.); Architects; Engineers